2009
DOI: 10.1111/j.1540-8159.2009.02495.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Psychoeducational Intervention on Depression, Anxiety, and Health Resource Use in Implantable Cardioverter Defibrillator Patients

Abstract: Background-Psychological responses have been reported for some patients after insertion of an implantable cardioverter defibrillator (ICD). This study tested the effects of a psychoeducational intervention on anxiety, depressive symptoms, functional status and health resource use during the first year after ICD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 60 publications
7
93
1
8
Order By: Relevance
“…Despite this, the mean functional capacity was high, with a DASI score of 48.1 (ceiling value, 58.2), corresponding to an estimated peak oxygen uptake of 30.3 mL/kg per minute, which was more favorable than those of other ICD populations (mean DASI score, 17-21). 13 This finding reflects the relative disconnect between arrhythmia risk and extent of structural and functional remodeling in ARVC.…”
Section: Article See P 18mentioning
confidence: 98%
See 2 more Smart Citations
“…Despite this, the mean functional capacity was high, with a DASI score of 48.1 (ceiling value, 58.2), corresponding to an estimated peak oxygen uptake of 30.3 mL/kg per minute, which was more favorable than those of other ICD populations (mean DASI score, 17-21). 13 This finding reflects the relative disconnect between arrhythmia risk and extent of structural and functional remodeling in ARVC.…”
Section: Article See P 18mentioning
confidence: 98%
“…Finally, exercise training as part of a comprehensive cardiac rehabilitation program has reduced anxiety and depression and improved quality of life in ICD patients. 16,17 However, these studies enrolled older adults (mean age, late 50s), and the largest one specifically excluded patients with genetic arrhythmias, 13 so it remains to be seen whether similar interventions will be equally feasible and successful at reducing anxiety and improving quality of life in ICD patients with ARVC and other inherited cardiac diseases.…”
Section: Article See P 18mentioning
confidence: 99%
See 1 more Smart Citation
“…ICD implantasyonu sonrası daha iyi psikolojik sonuçlar elde etmek için grup ve telefon müdahale-lerinin klinik kullanımını destekleyecek ileri çalışmaların yapılması önerilmektedir. Telefonla danışma ve takibin, akut ve ayakta bakım arasındaki uçurumu kapatabilecek, maliyet etkin ve klinik olarak uygulanabilir bir yaklaşım olduğu, bir merkeze uzak ve gruplara katılamayacak olan hastalar için sonuçları iyileştirmede yardımcı olabileceği belirtilmiştir (20).…”
Section: Telefonla İzlemunclassified
“…[75][76][77][78][79] Research has shown that 25% of ICD recipients experience depression or anxiety problems, 80 with the majority receiving no formal treatment for psychological problems. 81 Only 3 out of 44 patients in our study disclosed psychological problems attributable to device implantation, which is lower than previous research.…”
Section: Implications For the Development Of Decision-support Toolsmentioning
confidence: 99%